2021
DOI: 10.3390/math9212721
|View full text |Cite
|
Sign up to set email alerts
|

Synchronizability of Multi-Layer Variable Coupling Windmill-Type Networks

Abstract: The system model on synchronizability problem of complex networks with multi-layer structure is closer to the real network than the usual single-layer case. Based on the master stability equation (MSF), this paper studies the eigenvalue spectrum of two k-layer variable coupling windmill-type networks. In the case of bounded and unbounded synchronization domain, the relationships between the synchronizability of the layered windmill-type networks and network parameters, such as the numbers of nodes and layers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 28 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…With the deepening of the research, scholars have found that most complex systems are not isolated, but are instead interdependent and interactive. Researchers introduced the concept of multi-layer networks to describe such networks and have made fruitful achievements in the field of research on multi-layer networks, such as accomplishing the synchronization of multi-layer complex networks [6][7][8][9][10][11][12], structure identification of multi-layer networks [13], and cascading failures and consensus of multi-layer networks [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…With the deepening of the research, scholars have found that most complex systems are not isolated, but are instead interdependent and interactive. Researchers introduced the concept of multi-layer networks to describe such networks and have made fruitful achievements in the field of research on multi-layer networks, such as accomplishing the synchronization of multi-layer complex networks [6][7][8][9][10][11][12], structure identification of multi-layer networks [13], and cascading failures and consensus of multi-layer networks [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%